INTEREST IN ENTREPRENEURSHIP DRIVEN BY SELF-EFFICIENCY AMONG CIREBON STUDENTS USING SOCIAL MEDIA - Rahmadi Rahmadi; Yono Maulana (SEAN Institute, 2023)
This study aims to determine the impact of Feasibility and Self-Efficacy on Entrepreneurial Interest. This research was conducted at the Faculty of Economics, Universitas Swadaya Gunung Jati Cirebon, with a sample of 86 respondents. The determinant of respondents is chosen through proportional random sampling techniques because respondents are already known to the population and the distribution of the number of respondents who are even in each class. The data analysis method uses validity, reliability, classical assumptions, regression analysis, as well as t tests and F tests processed through the IBM SPSS 25 (Spescial Package For Statistical Science) application. The results showed that there was a partial significant positive impact of Feasibility and Self-Efficacy variables on Entrepreneurial Interest, simultaneously there was a significant positive impact of 61.8% between the Feasibility and Self-Efficacy variables on Entrepreneurial Interest, and the remaining 38.2% influenced by other factors. For the university, it is important to pay attention to the applicable curriculum and increase the intensity of entrepreneurship training programs as an implementation so that many students are interested in becoming an entrepreneur.